Esterification of palm fatty acid distillate for biodiesel production catalyzed by synthesized kenaf seed cake-based sulfonated catalyst - Akinfalabi, Shehu-Ibrahim; Rashid, Umer; Choong, Thomas Shean Yaw; Nehdi, Imededdine Arbi; Sbihi, Hassen Mohamed; Gewik, Mohamed Mossad (MDPI, 2019)
Sulfonated kenaf seed cake (SO3H-KSC) catalyst, was synthesized to aid biodiesel production from palm fatty acid distillate (PFAD). It was chemically activated with phosphoric acid for an impregnation period of 24 h in order to enhance the porosity and the specific surface area of kenaf seed cake (KSC). After the carbonization and sulfonation, the resultant catalyst was characterized with powder X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), Fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscope (FESEM), NH3-temperature programmed desorption (NH3-TPD) and thermogravimetric analysis (TGA). The SO3H-KSC catalyst was amorphous in nature and had an acid density of 14.32 mmol/g, specific surface area of 365.63 m2/g, pore volume of 0.31 cm3/g and pore diameter of 2.89 nm. At optimum esterification conditions--reaction time 90 mins, temperature of 338 K, methanol:PFAD molar ratio of 10:1 and catalyst concentration of 2 wt.%—a free fatty acid (FFA) conversion of 98.7% and fatty acid methyl esters (FAME) yield of 97.9% was achieved. The synthesized SO3H-KSC catalyst underwent five reaction cycles while maintaining a fatty acid methyl esters (FAME) yield and free fatty acid (FFA) conversion of >90%. Thus, the SO3H-KSC catalyst was shown to be an excellent application of bio-based material as a precursor for catalyst synthesis for esterification of PFAD.